مقارنة طرائق تقدير معلمات توزيع كاما ذي المعلمتين في حالة البيانات المفقودة باستخدام المحاكاة - رشيد, ظافر حسين; وادي, اوات سردار (Journal of Economics and Administrative Sciences, 2008)
The estimation of the parameters of Two Parameters Gamma Distribution in case of missing data has been made by using two important methods: the Maximum Likelihood Method and the Shrinkage Method. The former one consists of three methods to solve the MLE non-linear equation by which the estimators of the maximum likelihood can be obtained: Newton-Raphson, Thom and Sinha methods. Thom and Sinha methods are developed by the researcher to be suitable in case of missing data. Furthermore, the Bowman, Shenton and Lam Method, which depends on the Three Parameters Gamma Distribution to get the maximum likelihood estimators, has been developed. A comparison has been made between the methods in the experimental aspect to find the best method through simulation by using the Monte Carlo Method. Several experimentations have been made by using the important statistical measure: Mean Square Error (MSE).